Pluralism and Religious Tolerance in Indonesia: An Ethical-Theological Review Based on Christian Faith Perspectives - Christian Siregar (Bina Nusantara University, 2016)
This article discussesed the discourse of pluralism and tolerance from a Christian perspective by understanding the scriptures of the Bible. The research applied library research. The study reached the conclusion that the understanding of pluralism and tolerance should be viewed positively and placed on the proportion of actual and be equipped concrete steps of interfaith dialogue and cooperation so as not to undermine the unity of the Indonesian nation and ultimately destructive to the life towards an impartial and prosperous society who represents the ideals of national life in our beloved republic. It is hoped this discussion can be a reference or evaluation of materials for readers to reduce the potential for horizontal conflict that often occurs among religious believers in Indonesia who use the name of belief/religious truth